2018
DOI: 10.7150/thno.22222
|View full text |Cite
|
Sign up to set email alerts
|

Desacetylvinblastine Monohydrazide Disrupts Tumor Vessels by Promoting VE-cadherin Internalization

Abstract: Vinca alkaloids, the well-known tubulin-binding agents, are widely used for the clinical treatment of malignant tumors. However, little attention has been paid to their vascular disrupting effects, and the underlying mechanisms remain largely unknown. This study aims to investigate the vascular disrupting effect and the underlying mechanisms of vinca alkaloids.Methods: The capillary disruption assay and aortic ring assay were performed to evaluate the in vitro vascular disrupting effect of desacetylvinblastine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 62 publications
1
12
0
Order By: Relevance
“…The mice for the MRI examinations were randomly divided into four groups and then intraperitoneally injected with normal saline (Group A or control group), bevacizumab (5 mg/kg; Group B), oxaliplatin (4 mg/kg; Group C), and oxaliplatin combined with bevacizumab (Group D) on days 1, 4, 7, 10, and 13. The tumor volume was calculated using the following formula: (a 2 × b × 0.5) mm 3 , where a refers to the smaller diameter and b is the diameter perpendicular to a, measured with a slide caliper (19). The tumor inhibition rate refers to (tumor size of untreated mice-tumor size of treated mice)/tumor size of untreated mice × 100%.…”
Section: Tumor Model and Groupingmentioning
confidence: 99%
“…The mice for the MRI examinations were randomly divided into four groups and then intraperitoneally injected with normal saline (Group A or control group), bevacizumab (5 mg/kg; Group B), oxaliplatin (4 mg/kg; Group C), and oxaliplatin combined with bevacizumab (Group D) on days 1, 4, 7, 10, and 13. The tumor volume was calculated using the following formula: (a 2 × b × 0.5) mm 3 , where a refers to the smaller diameter and b is the diameter perpendicular to a, measured with a slide caliper (19). The tumor inhibition rate refers to (tumor size of untreated mice-tumor size of treated mice)/tumor size of untreated mice × 100%.…”
Section: Tumor Model and Groupingmentioning
confidence: 99%
“…Previous studies suggested that thrombin increased the microvascular permeability by activating PAR1 pathway, which increased the activity of downstream protein kinases, such as p21‐activated kinase‐1 (PAK1) . Several lines of evidence also indicated that the phosphorylation of Src or PAK1 was involved in the degradation and loss of VE‐cadherin …”
Section: Introductionmentioning
confidence: 99%
“…19 Several lines of evidence also indicated that the phosphorylation of Src or PAK1 was involved in the degradation and loss of VE-cadherin. [22][23][24][25] In this study, we hypothesized that thrombin-induced hydrocephalus was related to the PAR1 signaling pathway which resulted in the decline of VE-cadherin in choroid plexuses. And this process may shed light on the formation of hydrocephalus after IVH.…”
mentioning
confidence: 98%
“…They were treated with normal saline (Group A), 4 mg/kg of doxorubicin (Group B), 2 mg/kg (Group C), and 4 mg/kg of cRGD-PLGA@DOX (Group D) via the tail vein once every 2 days. The tumor volume was calculated using the following formula: (a 2 × b × 0.5) mm 3 , where a refers to the smaller diameter and b is the diameter perpendicular to a, measured with a slide caliper ( 17 ). The tumor inhibition rate refers to (tumor size of untreated mice−tumor size of treated mice)/tumor size of untreated mice × 100%.…”
Section: Methodsmentioning
confidence: 99%